2017
DOI: 10.1089/lap.2016.0436
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Endoscopic Injection Sclerotherapy and Endoscopic Variceal Ligation in the Treatment of Esophageal Varices

Abstract: Both EIS and EVL produce excellent results, are safe, effective, feasible, and acceptable for EVB with minimum complications and obviate need for subsequent procedures in the short term. To make better choice, we should consider the hospital conditions, operator experience, and the characteristics of esophageal varices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 35 publications
0
28
0
2
Order By: Relevance
“…A variety of sclerosant solutions are used, the most common being ethanolamine oleate (5%), polidocanol (1%-2%), and cyanoacrylate, which proved equally effective for bleeding esophageal varices. 20 Emergency ES for bleeding esophageal varices was shown to be an effective procedure in expert hands 21 ; however, it is no longer recommended as the first line of treatment because of high complication rate (systemic bacteremia being the most frequent). 22 EVL is the standard care for management of AVB.…”
Section: Management Of the Acute Variceal Bleeding Episodementioning
confidence: 99%
“…A variety of sclerosant solutions are used, the most common being ethanolamine oleate (5%), polidocanol (1%-2%), and cyanoacrylate, which proved equally effective for bleeding esophageal varices. 20 Emergency ES for bleeding esophageal varices was shown to be an effective procedure in expert hands 21 ; however, it is no longer recommended as the first line of treatment because of high complication rate (systemic bacteremia being the most frequent). 22 EVL is the standard care for management of AVB.…”
Section: Management Of the Acute Variceal Bleeding Episodementioning
confidence: 99%
“…Although new varices formed following initial eradication in 31 of 50 (62%) patients in our study, this was associated with rebleeding in only 3 (9.7%) patients. Variceal recurrence in other studies ranged between 8% and 48% after banding[ 18 , 35 , 42 ]. More recent studies have shown recurrence rates of 12% to 36% (mean 25%) using EVL and NSBB[ 26 - 28 , 30 ].…”
Section: Discussionmentioning
confidence: 91%
“…Patient numbers in these studies, however, were small and there was no consistency in the definition of duration of control of active bleeding. In an updated analysis of 17 prospective randomized controlled trials (RCTs) comparing EVL with sclerotherapy, bleeding variceal control with EVL ranged from 86% to 100%, and was significantly better than IST in 2[ 19 , 20 ] of 17 RCTs[ 21 - 35 ] (Table 4 ). However, the reported efficacy of EVL in these RCTs varied widely due to arbitrary and inconsistent definitions of bleeding control[ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Аналізуючи дані щодо рандомізованих досліджень та метааналізів по первинній зупинці кровотечі із ВРВ стравоходу, в літературних джерелах стверджується, що ендоскопічна склеротерапія є ефективною у 90% хворих, використання зонда Блекмора -у 80-90% пацієнтів, застосування октреотиду -у 90-97%, виконання TIPS -у 90% [8,9]. Рецидив кровотечі протягом 5 діб відбувається відповідно у 17-37% хворих при використанні ендоскопічної склеротерапії, у 50% -балонної тампонади, 25% -октрестатину, у 30% -при використанні TIPS [10].…”
unclassified